الضغوط النفسية وعلاقتها بدافعية الانجاز لدى طلبة السنة الاولى جامعي بجامعة خميس مليانة - مركون, هبة (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى الكشف عن العلاقة الموجودة بين الضغط النفسي والدافعية للانجاز لدى طلبة السنة أولى جامعي، والكشف عن الفروق في الضغط النفسي والدافعية للانجاز تبعا لمتغيرات التخصص ومكان الإقامة، وهذا من خلال التطرق للموروث النظري السابق والاعتماد على المنهج الوصفي التحليلي .وبعد تطبيق الدراسة الميدانية من خلال تطبيق أدوات الدراسة لمقياس الضغط النفسي ومقياس والدافعية للانجاز لعينة الدراسة التي بلغت (100) طالب وطالبة، تم جمع البيانات والمعلومات المتحصل عليها من معالجتها إحصائيا باستخدام التقنيات الإحصائية ( تطبيق برنامج spss واختبار Tلعينتين مستقلتين وكذا معامل بارسون) وتم استخلاص جملة من النتائج نوجزها فيما يلي:-وجود علاقة ذات دلالة إحصائية بين الضغط النفسي والدافعية للانجاز لدى طلبة السنة أولى جامعي .-لا توجد فروق ذات دلالة إحصائية في الضغط النفسي تبعا لمتغير التخصص .-لا توجد فروق ذات دلالة إحصائية في والدافعية للانجاز تبعا لمتغير مكان الإقامة. The study aimed to reveal the relationship between psychological pressure and motivation to achieve achievement among first-year university students, and to reveal differences in psychological pressure and motivation to achieve according to the variables of specialization and place of residence, and this by addressing the previous theoretical heritage and relying on the descriptive analytical approach. During the application of the study tools for the psychological pressure scale and the scale and motivation for achievement of the study sample that amounted to (100) students, the data and information obtained from treating them statistically were collected using statistical techniques (applying the spss program and the T-test for two independent samples, as well as the Parson coefficient). The following: - There is a statistically significant relationship between psychological stress and motivation for achievement among first-year university students.- There are no statistically significant differences in psychological stress according to the variable of specialization.- There are no statistically significant differences in the motivation for achievement according to the variable of residence.
Psychological pressure and its relationship to motivation of achievement for firstyear university students
مقال
Keywords: للانجاز ، الطالب الجامعي، الضغط النفسي ، الدافعية ، الدافعية; Psychological pressure , Motivation , Motivation for achievement , University student